Adapting Blended Learning Models in Post-Pandemic Education Systems - Lucas Lima; Pedro Silva; Omar Khan (Yayasan Adra Karima Hubbi, 2025)
Background. The COVID-19 pandemic has significantly disrupted traditional education systems, forcing a rapid transition to online learning. This transition has highlighted the need for flexible and adaptive teaching methods, making blended learning models increasingly relevant. Blended learning, which combines face-to-face and online education, has emerged as a potential solution for post-pandemic education systems. Purpose. This study aims to explore how blended learning models can be adapted and implemented in post-pandemic education systems to enhance student engagement, accessibility, and learning outcomes. A mixed-methods approach was used, combining surveys and interviews with educators and students across various educational institutions. Method. The data were analyzed to assess the effectiveness, challenges, and perceptions of blended learning in post-pandemic contexts. Results. The results indicate that while blended learning models are perceived positively, challenges such as technological limitations, teacher training, and student motivation remain significant. However, schools and universities that successfully integrated blended learning models reported improvements in flexibility, student satisfaction, and academic performance. Conclusion. The study concludes that blended learning has the potential to transform education systems by offering a more personalized, accessible, and adaptable learning experience. For successful implementation, ongoing professional development for educators and investment in technology infrastructure are crucial.